2021
DOI: 10.3390/jcm10215036
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Treatment-Resistant Hypertension in Newly Treated Hypertensive Patients in the United Arab Emirates

Abstract: (1) Background: The present study aimed to analyze medication adherence and its effect on blood pressure (BP) control and assess the prevalence of treatment-resistant hypertension (TRH) among newly treated hypertensive patients in the United Arab Emirates (UAE); (2) Methods: A retrospective chart review was conducted to evaluate 5308 naïve hypertensive adults registered for the treatment across Abu Dhabi Health Services (SEHA) clinics in Abu Dhabi in 2017. After collecting data regarding basic details and BP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“… 53 In a recent study conducted in the UAE among patients with hypertension, the overall adherence to antihypertensive treatment was 42% while we documented a higher rate at 78% with 85% at suboptimal hypertension control. 27 The UAE has an incidence for major CVD is 12.7 per 1000 person-years, 54 with 25% of this cohort positively affirming CVD. Almost all of this cohort are being treated (97%) at least 80% have indicated that their CVD event is controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 53 In a recent study conducted in the UAE among patients with hypertension, the overall adherence to antihypertensive treatment was 42% while we documented a higher rate at 78% with 85% at suboptimal hypertension control. 27 The UAE has an incidence for major CVD is 12.7 per 1000 person-years, 54 with 25% of this cohort positively affirming CVD. Almost all of this cohort are being treated (97%) at least 80% have indicated that their CVD event is controlled.…”
Section: Discussionmentioning
confidence: 99%
“…25 Literature evidence suggests a higher rate of non-compliance with medications in patients with Diabetes 26 and Hypertension. 27 Medication compliance issues could lead to increased morbidity, mortality, and economic burden through hospitalization and increased costs due to chronic disease complications.…”
Section: Introductionmentioning
confidence: 99%
“…Although, treatment rates in Saudi Arabia are higher, compared with UAE and Iran (45% and 43%, respectively), the treatment rates in HICs were reported to be >70% [19,42]. Further, proportion of patients adhering to antihypertensive medications was reported to be low (22.5%) [22] similar to the ndings from other Middle Eastern countries like OPT (16.9%) [43], but was lower than UAE (42.0%) [44]. Likewise, a huge variation was observed in the proportion of patients achieving BP control (27.0%-45.0%) [10,19,23,24,29] while HICs including Canada and Germany reported higher BP control (50.0%-69.0%) [42].…”
Section: Hypertension: Gaps Along Patient Journey Touchpointsmentioning
confidence: 65%
“…Adopting a lower BP threshold for hypertension (≥130/80 mmHg) and setting stringent target BP goals emphasizes the importance of early preventive measures and non-pharmacological interventions. Despite this, studies continue to record inadequate control of BP [ 20 , 23 , 24 , 28 , 29 , 30 , 31 ] and show poor physician compliance with such guidelines [ 32 , 33 , 34 ]. The continental divide of guideline-recommended BP goals is reflected in our study and showed variations in achievement across hypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The study cohort, study population, inclusion and exclusion criteria, and baseline data including anthropometric and BP measurements were previously described in detail [ 24 ]. Briefly, a retrospective chart review was conducted to identify incident hypertensive adults registered for antihypertensive treatment across Abu Dhabi Health Services (SEHA) between 1 January 2017 and 31 December 2017, and each patient was retrospectively followed up for 6 months to assess their outcomes.…”
Section: Methodsmentioning
confidence: 99%